Niezrealizowany projekt gmachu szkoły św. Marii Magdaleny we Wrocławiu autorstwa Valentina von Saebischa - Marek Świdrak (Quart)
Valentin von Saebisch (1578–1657) is known in the history of Wrocław mainly as a city fortifier. However, in addition to attending to the city’s defences, he was also active there in the field of civil architecture. The aim of the article is to expand knowledge of Saebisch’s design commitment responding to the needs of Wrocław. The analysis performed relates to four drawings that can be dated to the period 1616–1618, comprehensively depicting the design of a grand building. The architectural forms proposed by Saebisch are distinguished by a stylistic language typical of him yet isolated in Silesia, characteristic of the elite architectural foundations developed in the Rudolphine architectural circle. The specificity of the faithfully portrayed details makes it possible to identify the drawing as an unrealised design for the St. Mary Magdalene School in the location to which the institution’s building was moved in the 18th century. Thus, Saebisch’s identified project is a valuable source for research into the architecture of Wrocław at the dawn of the Thirty Years’ War, as well as the non-fortification activities that this architect carried out to meet the city’s needs.